International Project Management Association Research Conference 2017 (Broadway UTS ePRESS, 2017)
Conference papers from the International Project Management Association Research Conference (IPMA), held on 2-4 November 2017 in Incheon, Republic of Korea, hosted by IPMA-Korea. This year's theme was: Projects, management and success: do we need a new understanding?
English
Keywords: Project management; Business ethics & social responsibility; Operational research; Organizational theory & behaviour; History of specific companies / corporate history; Project management software; Project management software; Corporate history; History of specific companies; Organizational theory and behaviour; Business ethics and social responsibility; Operational research; Project management